Long-term follow-up results of prostate capsule-sparing and nerve-sparing radical cystectomy with neobladder: a single-center retrospective analysis - Zhu, Yiyi; Shi, Hongqi; Zhou, Penfei; Xue, Yadong; Hu, Shengye (Frontiers in Urology, 2024)
ObjectiveThis study aims to investigate and analyze the feasibility, oncological outcomes, functional efficacy, and complications with the prostatic capsule sparing (PCS) as well as the nerve sparing (NS) in radical cystectomy for bladder cancer.Patients and methodsBetween January 2007 and December 2021, 67 total cystectomies with PCS and 54 with NS were performed at our institution. The inclusion criteria for PCS were as follows: proactive, fully informed patient consent; negative transurethral resection of the bladder neck; normal prostate-specific antigen (PSA) level < 4 ng/dL; and normal transrectal ultrasonography with biopsy of any suspicious nodes. Patients received complete oncological and functional follow-ups. The Kaplan-Meier method was utilized to characterize survival outcomes after surgery.ResultsThe median follow-up times for PCS and NS were 144 and 122 months, respectively. Cumulative survival estimated the 5- and 10-years cancer-specific survival were 93.0% and 88.7% for the PCS group and 79.7% and 79.6% for the NS group, respectively (p = 0.123). In terms of function, the daytime urinary control at 3, 6, and 12 months postoperatively was 80.60%, 97.01%, and 100% in the PCS group, and 53.70%, 85.19%, and 94.44% in the NS group, respectively (p = 0.002, 0.023, and 0.100); and nocturnal urinary control was 62.69%, 94.03%, and 98.51% in the PCS group, and 40.74%, 72.22%, and 87.04% in the NS group, respectively (p = 0.016, 0.001, and 0.022). The erectile function recovery revealed that 62.69% and 40.74% of patients returned to preoperative levels (International Index of Erectile Function (IIEF)-5 score ≥ 15) in the PCS and NS groups, respectively (p = 0.016). Considering complications within 30 days after surgery, 4.48% and 7.69% patients had Clavien ≥ III complications in the PCS and NS groups, respectively (p = 0.700).ConclusionThe PCS provides better restored urinary control and sexual function than the NS technique and does not affect oncological outcomes. However, PCS is prone to bladder-neck obstruction complications and requires closer long-term follow-up.